2009
DOI: 10.1007/s00198-009-1018-7
|View full text |Cite
|
Sign up to set email alerts
|

Immune changes in post-menopausal osteoporosis: the Immunos study

Abstract: Our results suggest that, regardless of age and estrogen status, postmenopausal OP is associated with immune changes, highlighting a possible role of IFN-gamma in the pathophysiology of OP and reporting, for the first time, changes in several B lymphocyte populations. These alterations may reflect the frailty observed after fracture, providing new insight into the mechanisms of morbidity and mortality associated with OP fractures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
54
1
5

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 74 publications
(63 citation statements)
references
References 44 publications
3
54
1
5
Order By: Relevance
“…Nevertheless, changes in several B lymphocyte populations in patients affected by postmenopausal osteoporosis regardless of their estrogen status have been shown. 51 The role of B cells in the control of bone turnover has been studied in other diseases that affect bone, such as RA 48,52 and periodontal inflammation. 53 These studies suggest that B cells may be involved in the control of bone turnover in humans as well, mainly by the production of cytokines such as OPG and RANKL.…”
Section: Inflammatory Diseases Immune System and Bonementioning
confidence: 99%
“…Nevertheless, changes in several B lymphocyte populations in patients affected by postmenopausal osteoporosis regardless of their estrogen status have been shown. 51 The role of B cells in the control of bone turnover has been studied in other diseases that affect bone, such as RA 48,52 and periodontal inflammation. 53 These studies suggest that B cells may be involved in the control of bone turnover in humans as well, mainly by the production of cytokines such as OPG and RANKL.…”
Section: Inflammatory Diseases Immune System and Bonementioning
confidence: 99%
“…It affects one out of three women after menopause (Breuil et al, 2010). Oestrogen deficiency leads to an uncoupling between activity of bone resorbing cells (osteoclasts) and bone forming cells (osteoblasts) responsible for accelerated bone loss.…”
Section: Osteoporosismentioning
confidence: 99%
“…The concept of osteoimmunology recently emerged from increasing evidence of intimate links between bone tissue and the immune system. Indeed, recent studies have suggested that the increase in bone resorption induced by oestrogen deficiency is at least partly mediated by increased paracrine production of bone resorbing cytokines (Breuil et al, 2010). Multiple soluble mediators of immune cell function, including cytokines, chemokines and growth factors also regulate osteoblast and osteoclast activity.…”
Section: Osteoporosismentioning
confidence: 99%
See 2 more Smart Citations